2018
DOI: 10.7554/elife.32517
|View full text |Cite
|
Sign up to set email alerts
|

Thalamocortical and corticothalamic pathways differentially contribute to goal-directed behaviors in the rat

Abstract: Highly distributed neural circuits are thought to support adaptive decision-making in volatile and complex environments. Notably, the functional interactions between prefrontal and reciprocally connected thalamic nuclei areas may be important when choices are guided by current goal value or action-outcome contingency. We examined the functional involvement of selected thalamocortical and corticothalamic pathways connecting the dorsomedial prefrontal cortex (dmPFC) and the mediodorsal thalamus (MD) in the behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 43 publications
9
77
2
Order By: Relevance
“…This feedback is hypothesized to occur through recurrent feedback circuitry via thalamocortical projections. Interestingly, asymmetrical lesions of the thalamocortical connection between the MD and the PL prevents goaldirected learning (Bradfield et al, 2013b;Alcaraz et al, 2018), a result that mirrors PL-pDMS disconnection . It is an attractive hypothesis that, during instrumental learning, the MD sends response feedback to the PL to update the response-outcome contingency, which is integrated with BLA inputs in the pDMS to drive goal-directed learning.…”
Section: Feedback Circuits: Integrating Performance Signals Into Ongomentioning
confidence: 97%
See 2 more Smart Citations
“…This feedback is hypothesized to occur through recurrent feedback circuitry via thalamocortical projections. Interestingly, asymmetrical lesions of the thalamocortical connection between the MD and the PL prevents goaldirected learning (Bradfield et al, 2013b;Alcaraz et al, 2018), a result that mirrors PL-pDMS disconnection . It is an attractive hypothesis that, during instrumental learning, the MD sends response feedback to the PL to update the response-outcome contingency, which is integrated with BLA inputs in the pDMS to drive goal-directed learning.…”
Section: Feedback Circuits: Integrating Performance Signals Into Ongomentioning
confidence: 97%
“…Like the PL, lesions of the MD disrupt the acquisition of goal-directed instrumental actions but not the expression of goal-directed instrumental behaviour (Ostlund & Balleine, 2008). Likewise, disconnection of these two structures prevents goal-directed learning (Bradfield et al, 2013b;Alcaraz et al, 2018). Indeed, recent pathway specific disconnection of the PL-MD and MD-PL projections has demonstrated that, at least with regard to the acquisition of contingency-related information, the projection from the MD-to-PL is particularly critical, suggesting that the MD could be one source of feedback to the PL necessary for encoding the response-outcome contingency.…”
Section: Striatal Bases Of Instrumental Conditioningmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3 shows the largest connected sub-graph of increased metastability detected by the NBS at a fixed threshold for all seven tasks where each node is scaled to reflect its relative importance within the sub-graph (the sum of its effect sizes). Cortical regions associated with top-down attentional/cognitive control (including fronto-parietal and dorsal attention networks) were the most active across the seven tasks along with thalamo-cortical interactions linked to memory, learning, and flexible adaptation (Alcaraz et al, 2018;Wolff and Vann, 2018). Increases in metastability were more widespread than equivalent increases in synchrony…”
Section: Task Related Increases In Metastability Between Resting Statmentioning
confidence: 99%
“…The long-lasting gene expression and negligible impact on the physiology of neurons make CAV a competent vector when expressing effectors for functional analyses. Indeed, CAV-Cre mediated the expression of effectors for chemogenetics (Augur et al, 2016;Roth, 2016;Alcaraz et al, 2018;Ramanathan et al, 2018), genetic ablation (Liu et al, 2016), and calcium imaging (Otis et al, 2017(Otis et al, , 2019 for an intermediate time window, ranging from 2 weeks to a couple of months. Beyond 2 months, CAV can steadily express effectors for longer term functional analysis.…”
Section: Beneficial Properties Of Cav For Circuit Analysismentioning
confidence: 99%